Question Number 104419 by Anindita last updated on 21/Jul/20

Now the sum of your father and your is  90 years. 5 years ago your father′s age  was 3 times than your age. Write the  your age and your father′s age 3 years  after.

Answered by 1549442205PVT last updated on 22/Jul/20

Call x,y be your age and your father 3 years after  respectively.From the hypothesis we  have  { ((x+y−6=90)),((((y−8)/(x−8))=3)) :} ⇔ { ((x+y=96)),((3x−y=16)) :}  ⇔ { ((x+y=96)),((4x=112)) :} ⇔ { ((x=28)),((y=68)) :}  Hence,now you are 25 year− olds and your  father is 65 year−olds

Commented byRasheed.Sindhi last updated on 22/Jul/20

x+y−6^(???) =90

Commented by1549442205PVT last updated on 23/Jul/20

it is (x−3)+(y−3)=90 sir!thank you

Answered by Rasheed.Sindhi last updated on 23/Jul/20

   Using one variable   determinant ((,(your age),,(father′s age)),((−−−−),(−−−−),−,(−−−−−)),((Now),(       x),,(      90−x)),((5_(years) ago),(    x−5),,(      85−x)),((−−−−),(−−−−),−,(−−−−−)),(,(  3(x−5)),=,(85−x)),((Equation),(             4x),=,(85+15)),(,(                x),=,(25)),(,(      90−x),=,(65)),((−−−−),(−−−−),−,(−−−−−)),((Result),(         25),,(        65)))     After 3 years:  your age=25+3=28 years  your father′s age 65+3=68  years